A survey study of psychological Stress among sports coaches in various sports - Farhood, Nidaa Yasir; Zwayen, Jinan Naji; Nasser, Abduljaleel Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the causes of stress for different sports coaches according to the dimensions of the scale used by researchers, which are the causes and factors associated with players or the sports team, causes or factors related to the characteristics of the sports coach and his personality, causes related to the senior management of players or the team, causes or factors related to the media, and finally reasons or Factors related to the fans, the researchers used the descriptive approach and were chosen from (30) different game coaches, and through the results it appeared that the most important causes of psychological stress for the coaches are reasons related to the top management of players or the team, and came in the Zantian level in terms of importance, reasons related to players or The sports team, either in the third rank of the causes of psychological pressure for the coaches represented by the reasons related to the senior management of the players or the team, and the reasons related to the media came fourth, and the weakest reasons were represented by the fans.